Pharmacist involvement in combating the opioid crisis: A mixed‐methods approach revealing conflicting perceptions. Issue 1 (21st May 2019) - Blue, Heather; Hawthorne, Amanda N.; Melgaard, Kelsey; Dahly, Ashley; Lunos, Scott; Palombi, Laura
Abstract: Introduction: Although the opioid crisis has been acknowledged as a public health emergency that requires collaboration and engagement from pharmacists, the perceptions of pharmacists on their role in harm reduction strategies and their views on opioid use have not been well established. Objectives: The primary objective of this study was to understand Minnesota pharmacists' attitudes about the profession's role in the opioid crisis, including perceptions on the pharmacist's public health and clinical roles within the crisis, views on the dispensing of naloxone, and attitudes toward harm reduction strategies including syringe access. Methods: This was a mixed‐method study that utilized an anonymous email survey containing Likert‐type responses which were quantitatively analyzed, as well as open comment boxes evaluated using Consensual Qualitative Research (CQR) methods. Pharmacists with a Minnesota license from all practice settings were invited to participate in the survey. Results: While the majority of participating pharmacists acknowledged a need within their communities to address the opioid epidemic agreeing that the profession should have a role in the community response, including provision of patient education and naloxone distribution, a small number of pharmacists believed that either the epidemic was not pertinent to their practice or pharmacy as a profession should not be involved. Concerns regarding naloxone included lack of support from other health professionals, time constraints in practice, and safety and liability concerns with naloxone. Conclusion: Considerable opportunity for increased pharmacist education on both opioid use disorder and the role of the pharmacist in harm reduction initiatives exists. Pharmacists from a wide variety of clinical practice settings have appreciable potential to influence the opioid crisis by embracing their clinical and public health roles.